2021
DOI: 10.1038/s41523-021-00277-x
|View full text |Cite
|
Sign up to set email alerts
|

Heparanase: a potential marker of worse prognosis in estrogen receptor-positive breast cancer

Abstract: Heparanase promotes tumor growth in breast tumors. We now evaluated heparanase protein and gene-expression status and investigated its impact on disease-free survival in order to gain better insight into the role of heparanase in ER-positive (ER+) breast cancer prognosis and to clarify its role in cell survival following chemotherapy. Using pooled analysis of gene-expression data, we found that heparanase was associated with a worse prognosis in estrogen receptor-positive (ER+) tumors (log-rank p < 10−10) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 48 publications
1
8
0
Order By: Relevance
“…Heparanase enzyme is preferentially expressed in obesity-associated breast tumors in clinical/experimental settings [ 30 ] and associated with worse prognosis in ER+, but not ER− BC [ 52 ]. Heparanase is the only known mammalian endoglycosidase capable of cleaving heparan sulfate (HS) at the cell surface and ECM.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Heparanase enzyme is preferentially expressed in obesity-associated breast tumors in clinical/experimental settings [ 30 ] and associated with worse prognosis in ER+, but not ER− BC [ 52 ]. Heparanase is the only known mammalian endoglycosidase capable of cleaving heparan sulfate (HS) at the cell surface and ECM.…”
Section: Resultsmentioning
confidence: 99%
“…Of note, although heparanase is expressed by both Mϕ [ 46 , 47 , 48 , 49 ] and BC cells [ 52 ] numerous observations have repeatedly indicated that in the setting of breast tumors, carcinoma cells per se appear to represent the major cellular source of the enzyme (reviewed in [ 52 ]). Given the above notion, the secreted nature of heparanase, and the role of extracellular heparan sulfate in modulation of TLR signaling ([ 80 , 81 , 82 ]), it is plausible that in the BC under obese conditions the excessive enzyme overexpressed by the tumor cells is a main contributor to adverse activation of macrophages.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Heparin, exclusively produced by mast cells, is a more sophisticated and sulfated form of HS. Early studies evidenced HS’s higher charged congener unfractionated heparin (UFH) as an efficient heparanase inhibitor and as a substrate [ 28 , 29 , 30 , 31 ]. Early studies showed effective heparanase inhibition by UFH, even if some UFH sequences can be recognized and cleaved by heparanase [ 32 ].…”
Section: Introductionmentioning
confidence: 99%